Preliminary Acute and Subchronic Toxicity Studies of GLG-V-13, a Novel Class III Antiarrhythmic Agent, in Mice - Chen, Chun-Lin; Chandra, Sundeep A M; Kim, Soochong; Sangiah, Subbiah; Chen, Hao; Roder, Joseph D; Quails, Charles W, Jr.; Garrison, Gregory L; Cowell, Rick L; Berlin, Kenneth D; Scherlag, Benjamin J; Lazzara, Ralph (Arzneimittelforschung, 2000)
The acute and subchronic toxic effects of GLG-V-13 (3-[4-(1H-imidazol-l-yl)benzoyl]-7-iso-propyl-3,7-diazabicyclo[3.3.1]nonane dihydroperchlorate, CAS 155029-33-7), a novel class III with some class Ib antiarrhythmic activity, were investigated in mice. The estimated LD50 for GLG-V-13 given orally were 419 mg/kg for male mice and 383 mg/kg for female mice, respectively. The acute toxic signs appeared to be of the central nervous system in origin. Four groups of mice (15 per sex, group and dose) were fed daily with diets containing GLG-V-13 for 90 consecutive days. The equivalent daily doses were 0, 22, 50 and 121 mg/kg/day and 0, 27, 60 and 136 mg/kg/day for male and female mice, respectively. All of the mice survived. Food consumption was decreased. However, mean body weight and body weight gain were not significantly changed. Gross pathological changes, especially in the lungs and liver, were found in the middle and high dose groups. Consistent increased mean corpuscular hemoglobin concentration and decreased mean corpuscular hemoglobin were observed in all dose groups. Hepatocellular necrosis was found in both male and female mice treated with the drug and was dose-dependent. Marked vacuolation of the X zone in the adrenal gland with mild to moderate deposition of ceroid pigments (brown degeneration) was observed in female mice. Lesions in the kidneys and adrenal glands may be a possible reason for changes in serum sodium and potassium ions concentrations leading to an increase in water intake. A significant reduction in cholesterol in the high dose group may be a favorable pharmacological effect of GLG-V-13. The data from the 90-day subchronic toxicity studies indicate that GLG-V-13 appears to have limited systemic toxicity potential.
Keywords: Antiarrhythmics, combined class Ib and class III; CAS 155029-33-7; GLG-V-13, mice, toxicity studies; 3-[4-(1H-Imidazol-1-y1)benzoyl]-7-isopropyl-3,7-diazabicyclo [3.3.1]nonane dihydroperchlorate